A Southeast Asian Perspective on the COVID-19 Pandemic: Hemoglobin E (HbE)-Trait Confers Resistance Against COVID-19 - Papadopoulos, Konstantinos I. (Med Sci Monit Basic Res, 2021)
As of November 25, 2020, over 60 million people have been infected worldwide by COVID-19, causing almost 1.43 million deaths. Puzzling low incidence numbers and milder, non-fatal disease have been observed in Thailand and its Southeast (SE) Asian neighbors. Elusive genetic mechanisms might be operative, as a multitude of genetic factors are widely shared between the SE Asian populations, such as the more than 60 different thalassemia syndromes (principally dominated by the HbE trait). In this study, we have plotted COVID-19 infection and death rates in SE Asian (SEA) countries against heterozygote HbE and thalassemia carrier prevalence. COVID-19 infection and death incidence numbers appear inversely correlated with the prevalence of HbE and thalassemia heterozygote populations. We posit that the evolutionary protective effect of the HbE and other thalassemic variants against malaria and the dengue virus may extend its advantage to resistance to COVID-19 infection, as HbE heterozygote population prevalence appears to be positively correlated with immunity to COVID-19. Host immune system modulations induce antiviral interferon responses and alter structural protein integrity, thereby inhibiting cellular access and viral replication. These changes are possibly engendered by HbE carrier miRNAs. Proving this hypothesis is important, as it may shed light on the mechanism of viral resistance and lead to novel antiviral treatments. This development can thus guide decision-making and action to prevent COVID-19 infection.